Antihyperglycemic and Antihyperlipidemic of Karala (Momordica charantia) Fruits in Streptozotocin Induced Diabetic Rats (Journal of Environmental Science and Natural Resources, 2012)
To investigate the antihyperglycemic and antihyperlipidemic effect of Momordica charantia (Karala), the aqueous extract of the Karala fruit was tested on streptozotocin (STZ)-induced diabetic rats. Thirty six albino rats were used in the experiment, 30 diabetic and the remaining six as negative control (T1). Diabetes was induced by administering (injecting) STZ at dose of 55mg/kg body weight. Thirty diabetic animals were randomly divided into five groups such as diabetic control group (T2) without any application of treatment, and groups T3,T4,T5 and T6 were treated with aqueous extract of Karala fruits daily at the doses of 250,    500 and 750mg/kg and glibenclamide (at a dose of 5mg/kg body weight) respectively. The body weight was taken and blood samples were collected from individual animal to determine glucose levels at 15 day interval up to 90 days. In addition, Asparate  Transaminenase(AST), Alanine Transaminenase(ALT), Alkaline Phosphatase(ALP), Total cholesterol (TCh) and Triglyceride (TGA) were determined at day 15 and at the end of the experiment. All three doses of Karala extracts reduced diabetic induced blood sugar and the reduction is comparable with standard glibenclamide (GLM) dose particularly with higher doses Karala extracts (500 and 750mg). Karala also prevented body weight loss due to induced diabetes as did by GLM treatment.. The treatment also resulted in a significant reduction of Asparate Transaminenase(AST), Alanine Transaminenase(ALT), Alkaline Phosphatase(ALP), Total cholesterol (TCh) and Triglyceride (TGA) activities of treated rats when compared to the STZ induced  diabetic rats. Higher doses of Karala (500 and 750mg/kg) are as effective as standard GLM dose on measured variables. This study demonstrated that Karala has hyperglycemia and antihyperlipidemic effect against STZ induced diabetic rats. These findings open the possibility of using Karala extract to treat diabetic animal and human patients although further research is warranted. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11550 J. Environ. Sci. & Natural Resources, 5(1): 29 - 37, 2012